Hypoxia signaling pathways: modulators of oxygen-related organelles - Schönenberger, Miriam J.; Kovacs, Werner J. (Frontiers in Cell and Developmental Biology, 2015)
Oxygen (O2) is an essential substrate in cellular metabolism, bioenergetics, and signaling and as such linked to the survival and normal function of all metazoans. Low O2 tension (hypoxia) is a fundamental feature of physiological processes as well as pathophysiological conditions such as cancer and ischemic diseases. Central to the molecular mechanisms underlying O2 homeostasis are the hypoxia-inducible factors-1 and -2 alpha (HIF-1a and EPAS1/HIF-2a) that function as master regulators of the adaptive response to hypoxia. HIF-induced genes promote characteristic tumor behaviors, including angiogenesis and metabolic reprogramming. The aim of this review is to critically explore current knowledge of how HIF-a signaling regulates the abundance and function of major O2-consuming organelles. Abundant evidence suggests key roles for HIF-1a in the regulation of mitochondrial homeostasis. An essential adaptation to sustained hypoxia is repression of mitochondrial respiration and induction of glycolysis. HIF-1a activates several genes that trigger mitophagy and represses regulators of mitochondrial biogenesis. Several lines of evidence point to a strong relationship between hypoxia, the accumulation of misfolded proteins in the endoplasmic reticulum, and activation of the unfolded protein response. Surprisingly, although peroxisomes depend highly on molecular O2 for their function, there has been no evidence linking HIF signaling to peroxisomes. We discuss our recent findings that establish HIF-2a as a negative regulator of peroxisome abundance and suggest a mechanism by which cells attune peroxisomal function with O2 availability. HIF-2a activation augments peroxisome turnover by pexophagy and thereby changes lipid composition reminiscent of peroxisomal disorders. We discuss potential mechanisms by which HIF-2a might trigger pexophagy and place special emphasis on the potential pathological implications of HIF-2a-mediated pexophagy for human health.